Kualitas Sumber Daya Manusia, Profesionalisme Kerja, Dan Komitmen Sebagai Faktor Pendukung Peningkatan Kinerja Karyawan PDAM Kabupaten Jember - Merisa Fajar Aisyah; Wiji Utami; Sunardi Sunardi; Sudarsih Sudarsih (UPT Penerbitan Universitas Jember, 2017)
This study aims to determine the effect of human resource quality, professionalism of work, commitment to employeeperformance PDAM Jember partially and simultaneously. Research approach used in this study is quantitative. Population inthe company amounted to 150 and taken 75 respondents to use the sample with the sampling method is simple randomsampling or simple random sample by means of a lottery / raffle of names of employees PDAM Jember is then taken assamples used lottery of 75 names of employees Selected in the draw. Methods of analysis using multiple linear regressionanalysis were used to determine the influence of strong between the dependent variable and independent variables. The testresults and analysis conducted states that the variable quality of human resources and a significant positive effect on employeeperformance PDAM Jember Regency. Variable professionalism and significant positive effect on employee performancePDAM Jember. And variable commitment and significant positive effect on employee performance PDAM Jember. And thequality of human resources, professionalism, and commitment to simultaneously positive and significant influence on employeeperformance PDAM Jember Regency.